Characterisation of infections in patients with acute myeloid leukaemia receiving venetoclax and a hypomethylating agent. (16th February 2022) - On, Sandy; Rath, Carolyn G.; Lan, Michelle; Wu, Bobby; Lau, Kimberly M.; Cheung, Edna; Alegria, William; Young, Rebecca; Tan, Marisela; Kim, Carrie; Phun, Jennifer; Patel, Nimish; et al.
Summary: We investigated the incidence of invasive fungal infections (IFIs) and other infectious complications in patients receiving venetoclax and hypomethylating agent therapy for acute myeloid leukaemia (AML). This retrospective, multicentre cohort study included adult patients with AML who received at least one cycle of venetoclax and either azacitidine or decitabine between January 2016 and August 2020. The primary outcome was the incidence of probable or confirmed IFI. Secondary outcomes included antifungal prophylaxis prescribing patterns, incidence of bacterial infections, and incidence of neutropenic fever hospital admissions. Among 235 patients, the incidence of probable or confirmed IFI was 5.1%. IFI incidence did not differ significantly according to age, antifungal prophylaxis use, or disease status. In the subgroup of patients with probable or confirmed IFIs, six (50%) were receiving antifungal prophylaxis at the time of infection. The overall incidence of developing at least one bacterial infection was 33.6% and 127 (54%) patients had at least one hospital admission for febrile neutropenia. This study demonstrated an overall low risk of developing probable or confirmed IFI as well as a notable percentage of documented bacterial infections and hospital admissions due to neutropenic fever.